Design of On Load Tap Changing Transformer (OLTC) to Increase Photovoltaic Penetration Level in Low Voltage Distribution Feeder - Radhiah Radhiah (Jurnal Teknologi, 2021)
This paper investigates a method for regulating the voltage profile and reducing the voltage unbalance at low voltage (LV) residential feeders with single-phase rooftop photovoltaic (PV) installed randomly along with the feeders. The used algorithm considers the distribution transformers that have on-load tap changers (OLTC) and can automatically control the voltage to prevent voltage rise in the feeder. MATLAB-based simulation results demonstrate the effectiveness of the discussed approaches.